Impact of comorbid personality disorder on violence in psychosis: report from the UK700 trial. - Moran, P; Walsh, E; Tyrer, P; Burns, T; Creed, F; Fahy, T (2003)
BACKGROUND: The impact of comorbid personality disorder on the occurrence of violence in psychosis has not been fully explored. AIMS: To examine the association between comorbid personality disorder and violence in community-dwelling patients with psychosis. METHOD: A total of 670 patients with established psychotic illness were screened for comorbid personality disorder. Physical assault was measured from multiple data sources over the subsequent 2 years. Logistic regression was used to assess whether the presence of comorbid personality disorder predicted violence in the sample. RESULTS: A total of 186 patients (28%) were rated as having a comorbid personality disorder. Patients with comorbid personality disorder were significantly more likely to behave violently over the 2-year period of the trial (adjusted odds ratio=1.71, 95% CI 1.05-2.79). CONCLUSIONS: Comorbid personality disorder is independently associated with an increased risk of violent behaviour in psychosis.